Evaluasi Kebijakan Pengembangan Potensi Pemuda oleh DISPORA Surabaya dalam Meningkatkan Partisipasi dan Kualitas Olahraga - Moh Gunawan Trismuwantara; Sapto Pramono; Sri Roekminiati; Aris Sunarya (Journal of Management and Social Sciences, 2025)
This study aims to evaluate the Youth Potential Development policy implemented by the Youth and Sports Office (DISPORA) of Surabaya in enhancing youth participation and the quality of sports among young people. In this research, the researcher employs Dunn's (2003) policy evaluation theory, which consists of six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The research method used is qualitative with a case study approach, and the data collected comes from interviews, documentation, and field observations related to the implementation of this policy. The findings indicate that the implemented policy has successfully increased youth participation in sports, with an increase of approximately 70% from the initial target. However, regarding the quality of sports performance, this policy faces challenges related to limited facilities and insufficient training, which hinder optimal achievement of performance. The conclusion of this study emphasizes that although DISPORA Surabaya has succeeded in increasing youth sports participation, the quality of sports performance still requires more attention, particularly in strengthening facilities and enhancing ongoing training. Additionally, there are several challenges that need to be addressed, such as the lack of adequate data, disparities in youth participation from different socio-economic backgrounds, and insufficient coordination among related agencies. Based on these findings, the researcher recommends that DISPORA Surabaya improve the data collection and information processing systems to be more integrated, design more inclusive policies for diverse youth segments, and strengthen coordination among related agencies to ensure that the policy is implemented more effectively and efficiently.